2021
DOI: 10.3390/pathogens10070879
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing Analysis to Identify Infection with Multiple Species of Nontuberculous Mycobacteria

Abstract: Mixed infection with multiple species of nontuberculous mycobacteria (NTM) is difficult to identify and to treat. Current conventional molecular-based methods for identifying mixed infections are limited due to low specificity. Here, we evaluated the utility of whole-genome sequencing (WGS) analysis to detect and identify mixed NTM infections. Analytical tools used included PubMLST, MetaPhlAn3, Kraken2, Mykrobe-Predictor and analysis of heterozygous SNP frequencies. The ability of each to identify mixed infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…The results of this study are also important for the clinical diagnosis of the disease, as they confirmed a higher diversity of M. abscessus in samples of lungs, chest wounds, and pleural fluid compared to sputum [52]. Sequencing data provided a more detailed subspecies classification in mixed cultures compared to conventionally used methods [53,54]. WGS also contributed to the finding of a high interspecies and intraspecies M. avium complex diversity in a patient with an ongoing pulmonary form of the disease.…”
Section: Wgs Perspectives For Diagnostics and Characterization Of Resistance Patterns Of Ntmsupporting
confidence: 59%
“…The results of this study are also important for the clinical diagnosis of the disease, as they confirmed a higher diversity of M. abscessus in samples of lungs, chest wounds, and pleural fluid compared to sputum [52]. Sequencing data provided a more detailed subspecies classification in mixed cultures compared to conventionally used methods [53,54]. WGS also contributed to the finding of a high interspecies and intraspecies M. avium complex diversity in a patient with an ongoing pulmonary form of the disease.…”
Section: Wgs Perspectives For Diagnostics and Characterization Of Resistance Patterns Of Ntmsupporting
confidence: 59%
“…Unfortunately, the correlation between mixed NTM infection and patient outcomes could not be investigated in our study due to the lack of data pertaining to clinical treatment. Misidentification of mixed NTM infection is not an uncommon finding, which can cause a critical problem in patient management 37 . Therefore, the future studies are needed to elucidate the clinical outcomes of mixed NTM infection with accurate diagnosis of single or mixed NTM infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical significance of mixed NTM species infection from the same patient is not fully understood yet, it is a frequent finding of NTM lung infection [ 35 ]. Disease status and clinical outcomes of patients with mixed NTM infection might be different from those with a single NTM infection [ 37 ]. Unfortunately, the correlation between mixed NTM infection and patient outcomes could not be investigated in our study due to the lack of data pertaining to clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, currently available software tools such as PubMLST, MetaPhlAn3, and Mykrobe-predictor showed variable performances in correctly identifying non-tuberculous mycobacterial species. Sensitivities ranged from 57–100% and specificities from 83–98%, which could be attributed to the different databases and algorithms used [ 50 ].…”
Section: Focus On Individual Microorganismsmentioning
confidence: 99%